PERSEPSI KEGIATAN EKSTRAKULIKULER KESENIAN TERHADAP MINAT DAN KREATIVITAS SISWA SD AL-HUDA SEMARANG - Nailul Fauzziyah; Aries Tika Damayani; Rofian Rofian (FKIP, PGSD, Universitas Slamet Riyadi, 2019)
This research aimed to determine the perceptual categories of art extracurricular activities in dance and painting on the interest and creativity of Al-Huda Elementary School students in Semarang. The method of this research was quantitative research with a type of descriptive approach. The research instrument was in the form of a questionnaire. The population in this study amounted to 65 students (35 dance students and 30 painting students). The test on the validity used a product moment correlation formula, the test on reliability used an alpha formula and the test on normality used lilifors formula. The results showed that perceptions of dancing extracurricular activities towards the interests was classified to the adequate category (51%), good (20%), less (29%). For the dancing extracurricular activities of dance towards the creativity of students, was classified to the good category (43%), sufficient (40%), less (17%). Whereas for painting extracurricular activities on students’ interest was classified to good (63%), sufficient (27%), less (10%). For painting extracurricular activities painting on the creativity of students was classified to the enough category (47%), good (30%), and less (23%).